Research on Countermeasures for Improving the Recovery Rate in the Later Stage of Steam Throughput Development in Ultra-Heavy Oil Reservoirs - Xiao, Xiao; Yao, Zhigang (International Journal of Natural Resources and Environmental Studies, 2025)
More than two decades after the development of Block D, it has entered the later stage of reservoir steam uptake development, and the difficulty of oil and gas exploration is increasing. To enhance the recovery rate of the block, countermeasures were studied in response to the current contradictions of poor steam injection effect, low formation energy, increased steam flow, uneven longitudinal utilization, and a large number of casing loss Wells. Planning and deployment were carried out to optimize steam injection parameters, implement carbon dioxide uptake, complement profile control technology measures, implement stratified steam injection and increase the intensity of major overhauls. In the field application process, the production effect was effectively improved. To propose development directions for high-cycle ultra-heavy oil blocks.